A Novel Act of Food Wastage Reduction by Distribution - Bhardwaj, Sharad; Kapoor, Simran; Singh, Smriti; Mandral, Vibhuti; Singhal, Pooja (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The purpose of Hunger Free is to free India from hunger. Every day over 20 crores Indians sleep without getting a meal. This problem can be solved by tackling the food wastage problem that occurs during big Indian weddings, Restaurants, etc. Hunger Free is a platform that provides a solution to this problem by connecting restaurants, various NGOs to the needy. Hunger Free is a web app designed and developed keeping in mind the difficulties NGOs or restaurants face to reach out to people.